(untitled) - David F Amstrong (New York, 1995)
This book proposes a radical alternative to dominant views of the evolution of language, and in particular the origins of syntax
Keywords: biolinguistics,gesture,grammar, comparative and general - syntax,language and languages - origin,sign language